Elementary Differential Equations and Boundary Value Problems 9th Edition

Published by Wiley
ISBN 10: 0-47038-334-8
ISBN 13: 978-0-47038-334-6

Chapter 2 - First Order Differential Equations - 2.1 Linear Equations; Method of Integrating Factors - Problems - Page 39: 14



Work Step by Step

Since in form of $\frac{dy}{dt}+ay=g(t)$ $\mu(t)=e^{2t}$ $e^{2t}y'+e^{2t}2y=e^{2t}e^{-2t}t$ $\frac{d}{dt}(e^{2t}y)=e^{-2t}e^{2t}t$ $\int{\frac{d}{dt}(e^{2t}y)}=\int{e^{0}t}$ $e^{2t}y=\frac{t^2}{2}+\frac{2c}{2}$ Constant 2c/2 can be simplified to c, since it can be any constant. $y=\frac{t^2+c}{2e^{2t}}$ Plug in $y=0, t=1$ $0=\frac{1+c}{2e^2}$ $c=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.